Effect of Inventory Management Practice on Organizational Efficiency: In Case Hawassa Tabor Ceramic Factory - Natnael H/mariam (My University, 2015)
This paper entitled as effect of inventory management practice on organizational efficiency. The general objective of the study is to investigate the practice of inventory management and its effect on organizational efficiency. The investigator of this study used quantitative approach of study especially descriptive and casual type of research. The investigator used random sampling specifically simple random one. The data collected from both primary and secondary sources. Method of data collection for primary research is survey and the data collected analyzed with the use of both descriptive and inferential statistics. Among the inferential statistics Pearson product moment correlation and multiple regressions used to show the relationship and effect between variables. The result from the study revealed that the practice of inventory management is not sufficient in the case company, inventory management has positive effect on organization efficiency and the extent variation it causes is 18.1%. Lastly, what the researcher recommended for the company is better if it manage inventory with consideration of all determinant variables with their specific techniques of management in detailed manner. Key words: Inventory management, organizational efficiency